Hilirisasi Aplikasi BangunAja untuk Optimalisasi Bisnis Lokal di Desa Santana Mekar - Amri, Teuku Khairul; Kashira, Frans Budi; Susanto, Fazry Rachman; Guntara, Rangga Gelar; Purwaamijaya, Btari Mariska (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The introduction of the BangunAja application in Santanamekar Village aimed to disseminate the design thinking method as an innovative approach to developing technology-based solutions. The primary objective was to provide a foundational understanding of design thinking and introduce the BangunAja application to the community as a user-centered design product. The implementation methods included theoretical material delivery, interactive discussions, and hands-on practice using the design thinking template provided by the BangunAja Team. This activity involved 20 participants from various community groups. The results showed that participants could understand the basic concepts of design thinking and apply them to simple case studies. Positive feedback indicated the application’s potential in supporting local solution development. The conclusion highlights the need for innovative approaches in community education and further application development tailored to local requirements.